Estimation of the winter bread wheat productivity according to the parameters of ecological adaptability in the southern forest-steppe of the Omsk region - V. M. Triputin; A. N. Kovtunenko; Yu. N. Kashuba (Зерновое хозяйство России)
The extension of winter bread wheat areas in Western Siberia is accompanied by the introduction of new varieties, the adaptive properties of which require careful evaluation. The purpose of the current work was to characterize the numbers of the Competitive Variety Testing (CVT) according to the parameters of ecological adaptability and stability. The objects of research through the years of 2016–2020 were 12 winter bread wheat samples from the CVT laboratory for winter grain crop breeding of the FSBSI “Omsk Agricultural Research Center”. The highest values of the linear regression coefficient were identified in the lines ‘22/16’, ‘24/16’, the varieties ‘Yubileinaya 180’, ‘Omskaya 4’ (bi = 1.15–1.19). The varieties ‘Priirtyshskaya’, ‘Priirtyshskaya 2’, the lines ‘38/17’, ‘47/16’, ‘42/18’ (bi = 0.81–89) reacted weaker to environmental changes. The lines ‘25/16’, ‘26/16’ and ‘43/18’ (bi = 1.01–1.02) had adaptability close to a unit. The most stable productivity was identified in the line ‘24/16’ (S2 d = 0.01). The similar productivity was provided by the variety ‘Priirtyshskaya’ and the lines ‘47/16’, ‘43/18’ (S2 d = 0.05–0.10). Among the less stable varieties were ‘Omskaya 4’, ‘Priirtyshskaya 2’, the lines ‘22/16’, ‘26/16’, ‘38/17’ (S2 d = 0.30–0.48). The variety ‘Priirtyshskaya’, the lines ‘38/17’, 43/18’ (V = 22.8–23.8%) had a relatively lower productivity variability. The line ‘43/18’ (5.70 t/ha) was the best in productivity. The varieties ‘Priirtyshskaya 2’ (5.29 t/ha), ‘Yubileinaya 180’ (5.19 t/ha), the lines ‘38/17’ (5.18 t/ha), ‘47/16’ (5.01 t/ha), the variety ‘Priirtyshskaya’ (4.85 t/ha) also had a significant excess over the standard variety ‘Omskaya 4’ (4.24 t/ha). In general, the estimation of the productivity adaptability has shown that the best numbers according to this trait are characterized by different reactions to growing conditions. The most productive line ‘43/18’ is adaptable. The variety ‘Yubileynaya 180’ is of intensive type. The response to environmental changes of the varieties ‘Priirtyshskaya’, ‘Priirtyshskaya 2’, the lines ‘38/17’, ‘47/16’ was weak.